2015
DOI: 10.1007/s00421-015-3305-7
|View full text |Cite
|
Sign up to set email alerts
|

Importance of mind-muscle connection during progressive resistance training

Abstract: Resistance-trained individuals can increase triceps brachii or pectarilis major muscle activity during the bench press when focusing on using the specific muscle at intensities up to 60 % of 1RM. A threshold between 60 and 80 % appeared to exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 18 publications
6
71
0
2
Order By: Relevance
“…In summary, the results of the present work indicate that the effects of attentional focus diminish when conventional deadlifts are performed at loading intensities that are close to an individual's one repetition maximum, which is consistent with previous literature attentional focus effects on muscle activation (Calatayud et al, 2016;Snyder & Fry, 2012). This was shown by the lack of significant differences between attentional foci for lift duration, peak barbell velocity and the kinetic measures (i.e.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In summary, the results of the present work indicate that the effects of attentional focus diminish when conventional deadlifts are performed at loading intensities that are close to an individual's one repetition maximum, which is consistent with previous literature attentional focus effects on muscle activation (Calatayud et al, 2016;Snyder & Fry, 2012). This was shown by the lack of significant differences between attentional foci for lift duration, peak barbell velocity and the kinetic measures (i.e.…”
Section: Resultssupporting
confidence: 92%
“…COP = centre of pressure COG = cognitive the results of the present work show no significant differences between an EF and an IF for lift duration (p > 0.05) and peak barbell velocity in the inferior-superior direction (p > 0.05). These findings suggest that attentional focus effects diminish at higher loading intensities, which is congruent with previous studies (Calatayud et al 2016;Snyder & Fry, 2012) that investigated the effects of IF instructions on muscle activity during multi-joint resistance exercises. Snyder & Fry (2012) and Calatayud et al (2016)'s findings both indicate a threshold between 60 to 80% of 1RM exists where adopting an IF no longer results in greater muscle activation relative to neutral instructions.…”
Section: Attentional Focus Effects On Conventional Deadlift Performancesupporting
confidence: 91%
See 2 more Smart Citations
“…On this kind of training, the verbal instruction (VI), composed by small phrases, helps to direct the practitioner to contract a specific muscle or muscle group 4 , as an attempt to emphasize its participation (e.g., focus on the contract the back muscles instead of the arms muscles). Recent studies have highlighted the importance of VI as a way to increase the myoelectric activity (EMG) 1,4,5 . Snyder and Leech 4 showed that VI focusing on the back musculature during the lat pulldown exercise, made the participants increase the latissimus dorsi activity in 17.6%.…”
Section: Introductionmentioning
confidence: 99%